Identification of Dominant Geo-Helminths in High Area of Anthropogenic Activities in Mubi North Local Govetment Area of Adamawa State - Adam, Muhammad M.; Ibrahim, Gadzama M.; Dawi, Wakawa A.; Okoye, Esther; Kabiru, Abubakar; Hamman, Amira (FUDMA Journal of Sciences, 2026)
Several factors responsible for the survival of geohelminths parasite such as temperature, soil quality, pH and rainfall as well as organic matter etc. geo-helminthes such as tape warm, rounds, earths and hook worms  etc. are parasites that thrives well in environment with poor sanitation. The samples used were obtained in dumpsite, farmland and virgin land during training and dry season. The samples were identification for geohelminths and physicochemical properties were analyzed. Results obtained shows that Ascaris lumbricoides (AL), Trichuris trichura (TT), Strongyloides stercoralis (SS) and Ancyclostoma duodenale were present during raining seasons with a mean score value of AL (1.00 – 14.67), TT (0.00 – 5.00), SS (0.00 – 6.67) and AD (0.00 – 11.67). The results of physicochemical properties of soil samples analyzed in raining and dry seasons in dumpsite, farmland and virgin land across Mubi North during raining season revealed that there were significant difference at (P< 0.05 %) level among the samples in terms of temperature, pH, E.C and O.M across the three locations where 9 samples were analyzed with mean value ranged from temperature, (35.10 – 35.90 oC) in dumpsite, (35.10 – 36.10 oC) in farmland and (35.10 – 36.80 oC) respectively.
Keywords: Soil; Geohelminths; Parasites; Physiochemical; Raining and Dry Season